1974
DOI: 10.1152/ajplegacy.1974.226.5.1142
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism of rabbit ileal mucosa

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Acetazolamide inhibits HCO3secretion in rat intestine in vivo (Parsons, 1956) but this effect was interpreted with caution because of the low activity of carbonic anhydrase in intestine (Kuriaki & Magee, 1964;Maren, 1967;Carter & Parson, 1971) and the apparently unrelated inhibitory effect of acetazolamide on Clabsorption. More recently Frizzell, Markscheid-Kaspi & Schultz (1974) reported that acetazolamide had no effect on the rate of HCO3production by stripped segments of rabbit ileum. In contrast the effectiveness of acetazolamide in inhibiting JHC03 in this study at concentrations low enough to avoid non-specific effects (Maren, 1977), and the presence of measurable amounts of carbonic anhydrase activity in the urodele intestinal epithelium (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Acetazolamide inhibits HCO3secretion in rat intestine in vivo (Parsons, 1956) but this effect was interpreted with caution because of the low activity of carbonic anhydrase in intestine (Kuriaki & Magee, 1964;Maren, 1967;Carter & Parson, 1971) and the apparently unrelated inhibitory effect of acetazolamide on Clabsorption. More recently Frizzell, Markscheid-Kaspi & Schultz (1974) reported that acetazolamide had no effect on the rate of HCO3production by stripped segments of rabbit ileum. In contrast the effectiveness of acetazolamide in inhibiting JHC03 in this study at concentrations low enough to avoid non-specific effects (Maren, 1977), and the presence of measurable amounts of carbonic anhydrase activity in the urodele intestinal epithelium (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Gallbladders were excised, opened and rinsed free of bile in control bathing solution at 0~ Since the oxygen consumption (0o2) of rabbit ileal mucosa was greatly depressed with the serosal musculature intact (Frizzell, Markscheid-Kaspi & Schultz, 1974), the muscle layers of gallbladder were removed 4 It is assumed from Fig. 6 that the spontaneous PD of each gallbladder is reduced by 25% due to reducing the Na concentration in the bathing solutions by 50% in the absence of a transmural ion gradient.…”
Section: Oxygen Consumption Measurementsmentioning
confidence: 99%
“…As indicated in Table I, ouabain (10-4 M) decreased I,, nearly to zero but had no effect on J" or on o 0 J. Tissue conductance decreased significantly below control levels but the decrease in oJ0S"m. was not statistically significant. Finally, in view of the observation that theophylline stimulates ionic secretory processes in intestine (7,18,5), the effect of this agent was studied with results shown in the last row of Table I. Theophylline (10-2 M) increased J:, significantly above the control level (P < 0.01) and significantly decreased both tissue conductance and Jdm.…”
Section: Properties Of J~cmmentioning
confidence: 99%